Some Aspects of Moose Domestication (Alces Alces L.) in Russia (Global Journal of Science Frontier Research, 2019)
Starting with ancient times, some historical stages of moose domestication in Russia are shown. A review of the results of our own research and published data of domestic and foreign authors for the 117-year period (from 1900 to 2018) is presented. Information from regional archival documents and materials of researchers that are not accessible to the general public is presented. It is shown that the moose has a number of positive qualities favoring its introduction to livestock. Due to the domestication of moose, man is given the opportunity to use moose resources more efficiently than by hunting, to obtain additional types of products and to conduct research and educational activities.
Keywords: moose; breeding; domestication; history